AFM and SEM Study on Crystallographic and Topographical Evolutions of Wet-Etched Patterned Sapphire Substrate (PSS): Part III. Cone-Shaped PSS Etched in H2SO4 and H3PO4 Mixture at Various Temperatures. (1st January 2017) - Shen, Jian; Zhang, Dan; Wang, You; Gan, Yang
Abstract : The effect of etching temperature (473–543 K) on the crystallographic and topographical evolutions as well as the etching rate of crystallographic planes of cone-shaped patterned sapphire substrate (PSS) etched in both H2 SO4 -based (H2 SO4 :H3 PO4 = 5:1 at volume ratio) and H3 PO4 etchants was systematically studied. For H2 SO4 -based etchant, higher temperature favors larger etching rate ratio of slant planes (S1 1 1 ¯ 0 5, S3 4 5 ¯ 1 38, S4 1 1 ¯ 0 12, and S5 1 ¯ 1 0 37 planes) to c -plane, thus leading to smaller filling factor (FF) of patterns; the Arrhenius activation energy ( E a ) of etching reactions for various crystallographic planes follows the order: E a ( c ) < E a (S1 ) < E a (S3 ) < E a (S4 ). For H3 PO4, higher temperature favors smaller etching rate ratio of slant planes (S1 1 1 ¯ 0 5 and S6 1 1 ¯ 0 8 planes) to c -plane and larger FF of patterns; the E a follows the order: E a (S1 ) < E a (S6 ) < E a ( c ). This work will contribute to elucidating the etching mechanism and fabricating optimized PSS for enhanced performance of light emitting diodes.